2020
DOI: 10.1158/0008-5472.can-19-3094
|View full text |Cite
|
Sign up to set email alerts
|

Dual Oxidase-Induced Sustained Generation of Hydrogen Peroxide Contributes to Pharmacologic Ascorbate-Induced Cytotoxicity

Abstract: Pharmacologic ascorbate treatment (P-AscH À , high-dose, intravenous vitamin C) results in a transient short-term increase in the flux of hydrogen peroxide that is preferentially cytotoxic to cancer cells versus normal cells. This study examines whether an increase in hydrogen peroxide is sustained posttreatment and potential mechanisms involved in this process. Cellular bioenergetic profiling following treatment with P-AscH À was examined in tumorigenic and nontumorigenic cells. P-AscH À resulted in sustained… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 47 publications
4
28
0
Order By: Relevance
“…We showed that 250 μM AA selectively induced cell death in primary leukemic CLL B-cells by acting as a pro-oxidant and thus by leading to the release of H 2 O 2 into the extracellular medium. These results are in compliance with previous observations in other cancers [ 5 , 12 , 14 ]. The cytotoxic effect of AA via H 2 O 2 generation was confirmed using an H 2 O 2 formation inhibitor (the iron chelator DFX) and two H 2 O 2 scavengers (catalase and SP).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We showed that 250 μM AA selectively induced cell death in primary leukemic CLL B-cells by acting as a pro-oxidant and thus by leading to the release of H 2 O 2 into the extracellular medium. These results are in compliance with previous observations in other cancers [ 5 , 12 , 14 ]. The cytotoxic effect of AA via H 2 O 2 generation was confirmed using an H 2 O 2 formation inhibitor (the iron chelator DFX) and two H 2 O 2 scavengers (catalase and SP).…”
Section: Discussionsupporting
confidence: 93%
“…Along with the superoxide anion (O 2 •− ) and the hydroxyl radical ( • OH), H 2 O 2 is a ROS. The literature data show that ROS (including H 2 O 2 ) mediate apoptosis through increasing the level of oxidative stress in cancer cells [ 14 , 15 , 52 ]. Indeed, targeting intracellular redox homeostasis by increasing ROS levels in cancer cells is a promising treatment approach [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 B–D) suggesting that peroxide mediates this effect. Previous studies from our laboratory have demonstrated that PDAC cells are viable at this time point 12 , 13 , which further supports the hypothesis that P-AscH − induced generation of H 2 O 2 mediates the inhibition of PDAC invasion as opposed to killing the cells which would indirectly inhibit invasion.
Figure 1 P-AscH − attenuates the invasive phenotype of PDAC in vitro .
…”
Section: Resultssupporting
confidence: 85%
“…Specifically, it has been postulated that the megadoses of AA, in the presence of metals, favor the Fenton reaction and the subsequent extracellular production of H 2 O 2 [ 7 , 31 , 32 , 86 ]. Diffusion of H 2 O 2 from the extracellular medium could be the trigger for an overwhelming overload of intracellular ROS, which would favor tumor death due to conventional necrosis [ 31 , 86 , 87 ]. It is important to note that this mechanism only works with megadoses of AA, because during the diffusion of H 2 O 2 , it is diluted 100-fold [ 88 ]; therefore, high concentrations of AA are needed to produce a lethal amount of H 2 O 2 .…”
Section: Regulation Of Cell Death By Vitamin Cmentioning
confidence: 99%